A participatory design approach based on the use of scenarios for improving local design methods in developing countries - GODJO, THIERRY; BOUJUT, Jean-François; Marouze, Claude; GIROUX, François (My University, 2015)
Over the past few years, the use of scenarios in participatory design has proved its worth. It has resulted in some interesting tools for capturing the context of use. However, these approaches have been almost exclusively developed and used for software design. In this article, we shall describe the development of scenarios in the specific context of tropical food processing equipment design in developing countries. As well as exploring this original field of application, this article raises fundamental questions about scenario use, taking us beyond the limited framework of the proposed application. We shall outline a methodological framework for structuring the deployment of scenarios according to the different design phases: the COSU method. This method implements the scenario concept in an original way. It comprises four types of scenario whose aim is to create interaction between designers and users in order to foster a shared understanding of both the problem and the solutions. We shall also show that the scenarios are objects that mediate the user-designer dialogue that is of prior importance in the context of developing countries. The applicability of the method is presented through various case study examples.
Keywords: Scenario Based design; Participatory Design; Collaborative Design; Food Processing Equipment; Developing Countries; Intermediary Design Object